Against Lung Cancer Cells: To Be, or Not to Be, That Is the Problem. (1st February 2012) - Okumura, Naoko; Yoshida, Hitomi; Kitagishi, Yasuko; Nishimura, Yuri; Iseki, Shio; Matsuda, Satoru
Abstract : Tobacco smoke and radioactive radon gas impose a high risk for lung cancer. The radon-derived ionizing radiation and some components of cigarette smoke induce oxidative stress by generating reactive oxygen species (ROS). Respiratory lung cells are subject to the ROS that causes DNA breaks, which subsequently bring about DNA mutagenesis and are intimately linked with carcinogenesis. The damaged cells by oxidative stress are often destroyed through the active apoptotic pathway. However, the ROS also perform critical signaling functions in stress responses, cell survival, and cell proliferation. Some molecules enhance radiation-induced tumor cell killing via the reduction in DNA repair levels. Hence the DNA repair levels may be a novel therapeutic modality in overcoming drug resistance in lung cancer. Either survival or apoptosis, which is determined by the balance between DNA damage and DNA repair levels, may lender the major problems in cancer therapy. The purpose of this paper is to take a closer look at risk factor and at therapy modulation factor in lung cancer relevant to the ROS.